Skin and hard surface disinfection against Candida auris – What we know today - Omardien, Soraya; Teska, Peter (Frontiers in Medicine, 2024)
Candida auris has emerged as a global healthcare threat, displaying resistance to important healthcare antifungal therapies. Infection prevention and control protocols have become paramount in reducing transmission of C. auris in healthcare, of which cleaning and disinfection plays an important role. Candida albicans is used as a surrogate yeast for yeasticidal claims of disinfection products, but reports have been made that sensitivity to disinfectants by C. auris differs from its surrogate. In this review, we aimed to compile the information reported for products used for skin and hard surface disinfection against C. auris in its planktonic or biofilm form. A comparison was made with other Candida species, and information were gathered from laboratory studies and observations made in healthcare settings.